2018
DOI: 10.1093/nar/gky525
|View full text |Cite
|
Sign up to set email alerts
|

N-terminal domain of human uracil DNA glycosylase (hUNG2) promotes targeting to uracil sites adjacent to ssDNA–dsDNA junctions

Abstract: The N-terminal domain (NTD) of nuclear human uracil DNA glycosylase (hUNG2) assists in targeting hUNG2 to replication forks through specific interactions with replication protein A (RPA). Here, we explored hUNG2 activity in the presence and absence of RPA using substrates with ssDNA–dsDNA junctions that mimic structural features of the replication fork and transcriptional R-loops. We find that when RPA is tightly bound to the ssDNA overhang of junction DNA substrates, base excision by hUNG2 is strongly biased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(56 citation statements)
references
References 51 publications
6
47
0
Order By: Relevance
“…It is plausible that the action of UNG is controlled by regulating its interaction with the hub proteins PCNA and RPA, which binds duplex DNA and ssDNA, respectively (Figure 8). The nuclear UNG1 variant, which lacks a PCNA binding site (Supplementary Figure S5), may be more dedicated to uracil in ssDNA, or alternatively to ssDNA-dsDNA junctions (20), through its interaction with RPA. In B cells such sites are present in RPA-stabilized ssDNA regions of the Ig loci that are targeted by AID (46) (Figure 8A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is plausible that the action of UNG is controlled by regulating its interaction with the hub proteins PCNA and RPA, which binds duplex DNA and ssDNA, respectively (Figure 8). The nuclear UNG1 variant, which lacks a PCNA binding site (Supplementary Figure S5), may be more dedicated to uracil in ssDNA, or alternatively to ssDNA-dsDNA junctions (20), through its interaction with RPA. In B cells such sites are present in RPA-stabilized ssDNA regions of the Ig loci that are targeted by AID (46) (Figure 8A).…”
Section: Discussionmentioning
confidence: 99%
“…The current paradigm is that UNG1 is transported to mitochondria where it is processed at the N-terminus by the mitochondrial processing peptidase (MPP) (17,18), while the UNG2 isoform is targeted to the nucleus. UNG2 can interact with PCNA by its N-terminal PIP-box motif (Figure 1) (19) or with RPA, to remove uracil at the replication fork (20). In addition, UNG2 is generally believed to be the isoform involved in CSR and SHM (4).…”
Section: Introductionmentioning
confidence: 99%
“…97100 Presumably, this mode of enzyme action allows hUNG2 to efficiently excise uracils that are incorporated opposite adenine during DNA replication. 101,102 Extensive mechanistic studies have been performed on uracil DNA glycosylase over the last 20 years to unravel its chemical mechanism, 85,89,90 structure, 73,103,104 and base-flipping mechanism, 73,89,90,105 making it one of the most well-understood DNA repair enzymes. More recently, a series of studies on its mechanism of DNA translocation have generated one of the most comprehensive pictures of facilitated diffusion that spans both in vitro and cell-based measurements.…”
Section: Dna Translocation By Dna Repair Glycosylasesmentioning
confidence: 99%
“…Although UNG efficiently excises uracil from ssDNA, at least in vitro , all downstream steps in BER require the dsDNA conformation to allow templated repair and to avoid formation of double strand breaks at the replication fork. Recent work from the laboratory of James T. Stivers demonstrated that RPA bound to ssDNA overhangs of junction DNA substrates mediated preferred targeting of UNG2 to uracil sites in the dsDNA region close to the junctions ( 31 ). This was likely facilitated by binding of UNG2 to RPA2 on the ssDNA overhangs.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, both UNG and RPA are required for somatic hypermutation (SHM) and class switch recombination (CSR) where they induce mutagenic processing of uracils generated by activation-induced cytidine deaminase (AID)-mediated deamination of cytosines in immunoglobulin (Ig) loci ( 35 ). The multiple functions of UNG are apparently regulated by its flexible N-terminal domain ( 31 , 36–42 ). UNG is expressed as two major isotypes, generally referred to as nuclear UNG2 and mitochondrial UNG1.…”
Section: Introductionmentioning
confidence: 99%